Strategic evaluation of recycling high-tech metals from urban mines in China: An emerging industrial perspective. (20th January 2019) - Zuo, Lyushui; Wang, Chang; Corder, Glen David
Abstract: High-tech minerals are essential for strategic emerging industries, and urban mines have become principal potential reservoirs of secondary high-tech mineral resources. In order to evaluate high-tech urban mines to understand their criticality and determine their potential and priority for high-tech minerals recovery, this paper develops a model with three dimensions - resource index, technology index, and environmental index. This model is applied to data from China, and a Monte Carlo simulation is conducted to estimate uncertainty. The results show that high-tech urban mines in China are divided into three clusters. The first cluster includes urban mines which have high scores in all three indices, they should be the top priority of collection and recycling. The second cluster covers high-tech urban mines with middle scores in resource index and technology index, and environmental index span from low to high. They are important second resources reservoirs of high-tech metals and should be paid significant attention. In the third cluster, high-tech urban mines have low scores in all three indices, they are not the focus of development but can't be ignored. Spent batteries, mobile phones and magnet motors are key reservoirs of high-tech metals. Furtherly, this paper presents that the evaluation model construction and evaluation results are deeply affected by consumption behavior, technology level, industrial development and the policy direction of the country. Based on the results, this paper proposes that urban mining should be treated as a national strategy to release the dual constraints of resources and environment, catalogue of key urban mining should be made, and to build a dynamic evaluation system and adjust the catalogue over time, and develop technologies for more effective and environment-friendly extraction material of urban mines. Graphical abstract: Highlights: A three-dimension model is developed to evaluate high-tech urban mines in China. High-tech urban mines in China are divided into three clusters. Spent batteries, mobile phones and magnet motors are key reservoirs of high-tech metals. The evaluation is deeply affected by country's actual conditions, and industrial characteristics.